Optimizing Postoperative Recovery: The Synergy between Physiotherapy, Nursing, Nutrition, and Pharmacy - Nasser Fahd Nasser Alsuroor, Fatimah SamitMuhanna Alrshidi‏, Munirah Nasser Fahad Alzaid2, Tehan Mohammed Mazeid Awaji‏, Aisha Hassan Ali Faqihi‏, Abdullah Saad Alotaibi‏,Obaid Bashir Mohammed Al-Tamimi, Shoq Raghian Alshammari; Abdulrahman Saud Saleh Aldawood (Journal of International Crisis and Risk Communication Research, 2024)
Introduction: Optimizing Patient Surgical Preparation in the Surgical Site and other Intraoperative Considerations: Much of the interdisciplinary efforts matter with preoperative patient preparation that can lead to excellent surgical results with fewer complications and better recovery results. It is also a real team effort: The program is briefed and administered by nurses, general surgeons, emergency medicine doctors, anesthetists, radiologists, pharmacy technicians, and other health care technicians. Each member contributes to a complete evaluation, a coordinated plan of action, and the skills to educate the patient, all of which are prerequisites to a successful surgical program. Aim of work: Toexplore the critical synergy between physiotherapy, nursing, nutrition, and pharmacy in optimizing postoperative recovery. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Optimizing, Postoperative Recovery, Synergy, Physiotherapy, Nursing, Nutrition, and Pharmacy. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:The postoperative is an important phase of a patient’s recovery process that should involve multidimensional and tertiary procedures. These aspects of physiotherapy, nursing, nutrition, and pharmacy to work hand in hand to help a patient get the best recovery prognosis with few complications and enhance the patient quality of life. The use of physiotherapy enhances the mobility status of the patients, prevents the development of complications as well as enhances the patient’s functional recovery in the future. Nursing involves constant patient checking, the management of pain, psychological support to the patient and enlightening the patient about his or her recovery progress. The function of nutrition is to afford the ingredients for body repair and immune defense, whereas pharmacy guarantees the proper utilization of drugs. These disciplines constitute a package care model that improves the results of a patient and speeds up the healing process. Encryption of these fields work hand in hand and in synergy would lead to better outcome and early recovery among patients undergoing surgeries.